THE IMPACT OF HYPERTENSION ON RENAL FUNCTION: A CLINICAL EVALUATION (International journal of artificial intelligence, 2026)
Hypertension is both a cause and consequence of chronic kidney disease (CKD). Elevated blood pressure leads to structural and functional changes in renal vasculature, ultimately impairing glomerular filtration. This study investigates the relationship between poorly controlled hypertension and renal function decline among adult patients in a clinical setting.